Caracterização dos beneficiários do programa Bolsa Família na cidade de Palmas – TO - Oliveira, Nilton Marques de (2021)
This article shows the main characteristics of benefited family units and determinants factors of exchange program for family (colled “Bolsa Família”) in Palmas City, Tocantins State (TO), Brazil. The methodology included interviews with beneficiaries by questionnaires application in units of Centros de Referência de Assistência Social-CRAS (Reference Centres for Social Assistance) in two extreme and opposite regions of the referred city, and 605 North, and Jardim Taquari, south region of Palmas, the capital city of Tocantins State. Results show mulatta or black mothers with more children than the average of the general population, with low education, and most unemployed, being the same profile for fathers. The beneficiaries fulfill the required conditions and use the money to buy mostly food, and do not have access to credit. They are people with low political and social participation in their communities and do not attend and do not have access to cultural goods. They are pleased for receiving the benefit, ignoring the additional shares of Bolsa Familia, considering being free people, happy, and believing in a better future.